SPORTS AS A MEANS TO ENHANCE STUDENTS' SELF-CONFIDENCE THROUGH OUTBOUND ACTIVITIES - Dicky Oktora mudzakir (Universitas Negeri Jakarta, 2025)
Background. Self-confidence is an important aspect of students' psychological development that can influence their academic achievement and social interactions. However, many students still exhibit low levels of self-confidence, particularly in the context of secondary education. Objectives. This study aims to investigate the effect of outdoor activities on improving students' self-confidence. Method. The method used is a quantitative experimental study with a pretest-posttest one-group design. The research subjects were 30 students from SMP Negeri 1 Lohbener, selected using purposive sampling with a quota sampling system. The instrument used was a self-confidence questionnaire consisting of 24 statements. Results. The analysis results showed a pretest average score of 86.73 and a posttest average score of 108.23, with an average score increase of 21.5. The t-test results indicated t-calculated = 7.447 and significance level (Sig.) = 0.000 < 0.05, indicating a significant difference between pre- and post-intervention scores. Conclusion. The conclusion of this study is that outdoor activities can significantly enhance students' self-confidence. The contribution of this research provides empirical evidence that experiential learning approaches, such as outdoor activities, can serve as an alternative strategy in fostering positive character development in students, particularly in building self-confidence and belief in their abilities.